2018
DOI: 10.1002/ccr3.1448
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic challenges in a patient with an occult insulinoma:68 Ga‐DOTA‐exendin‐4 PET/CT and 68Ga‐DOTATATE PET/CT

Abstract: Key Clinical MessageDespite growing evidence for GLP‐1R molecular‐based imaging, successful localization of insulinomas may require the use of multiple imaging modalities. Not all benign insulinomas express the GLP‐1R as expected. Our case demonstrates that there is a still an important role for traditional methods for the anatomical localization of an insulinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 8 publications
1
17
0
Order By: Relevance
“…This while malignant insulinomas often lack expression of GLP‐1R but have high expression of SSTR . This is reflected in various clinical imaging studies with exendin‐4–based tracers, where false‐negative cases were proven to be malignant insulinomas . Interestingly, also differences in uptake between primary tumor and metastases and uptake of both tracers in one lesion were observed, stressing the variability in molecular phenotype of insulinomas, which should be taking into account when selecting the appropriate tracer.…”
Section: Imaging Of Insulinoma With Exendin‐4–based Tracersmentioning
confidence: 99%
See 2 more Smart Citations
“…This while malignant insulinomas often lack expression of GLP‐1R but have high expression of SSTR . This is reflected in various clinical imaging studies with exendin‐4–based tracers, where false‐negative cases were proven to be malignant insulinomas . Interestingly, also differences in uptake between primary tumor and metastases and uptake of both tracers in one lesion were observed, stressing the variability in molecular phenotype of insulinomas, which should be taking into account when selecting the appropriate tracer.…”
Section: Imaging Of Insulinoma With Exendin‐4–based Tracersmentioning
confidence: 99%
“…Christ et al first performed clinical SPECT imaging using a peptide dose of 30 μg, whereas in later clinical studies, doses of approximately 2 to 17 μg were used and also higher specific activities were achieved . For PET imaging studies, peptide doses of 7 to 25 μg were injected, in which a wide range in peptide dose can be observed within and between studies . Most studies using SPECT tracers did not report side effects like hypoglycemia, nausea, or vomiting .…”
Section: Imaging Of Insulinoma With Exendin‐4–based Tracersmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously reported, in the other patient, the GLP-1R PET/CT scan result was more in keeping with a diagnosis of nesidioblastosis but at the time of surgery a discrete 8 mm lesion at the junction of body and the tail of the pancreas was resected with resolution of symptoms. 15 Retrospective review of this patient's Dotatate PET/CT scan following surgery in a centre specializing in neuroendocrine tumours suggested that the diagnosis of an insulinoma had been missed during the initial reporting of the scan. In all patients who underwent molecular-based functional imaging, the SIACST correctly localized the insulinoma.…”
Section: Patient Demographics and Clinical Features Are Summarized Inmentioning
confidence: 95%
“…Nevertheless, both SPECT and PET clinical studies demonstrated imaging of malignant insulinoma using exendin-4 analogues 26, 38, 39. Targeting both SSTRs and GLP-1Rs could provide complementary diagnostic value wherein negative scan using imaging agents comprising GLP analogues may potentially indicate malignancy 40.…”
Section: Introductionmentioning
confidence: 99%